IMPROVING STUDENTS’ SPEAKING ABILITY IN REPORTING PROCEDURAL TEXT BY USING VIDEOS - Kaniadewi Suci; Wachyu Sundayana; Pupung Purnawarman (Journal of English and Education, 2017)
The research investigated the use of video to improve students’ speaking ability in reporting procedural text to seven-graders of a junior high school in Bandung. A Quasi-experimental design was used in the research with pre-test-post-test non-equivalent group design. The experimental and control groups consisted of 25 students. Data collection was conducted by collecting students’ speaking on both pre-test and post-test and a set of questionnaire to experimental class. The data were analyzed using several tests in SPSS 20. The findings of the test and questionnaire showed that video was effective in improving students’ speaking scores. This condition was proven by statistical computation of independent t-test on post test scores in which tobt is higher than tcrit  ( 2.702 2.011 ).  This shows that video as media was considered effective to improve students’ speaking skills, particularly in speaking procedural texts. Finally, the findings from the questionnaire showed that most students gave positive responses toward this method. The students gained some benefits from this method such as helping them to improve language skills, creating an active and fun class, motivating them to participate in learning activities.